1998
DOI: 10.1097/00002800-199809000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Readmission Rates Through Discharge Interventions

Abstract: Readmissions to the hospital account for a significant number of all hospital admissions. Early discharge and inadequate care both during and after hospitalization are among the causes cited. Increasingly complex care and an aging population mandate that clinical nurse specialists (CNSs) in acute care settings assume more pivotal roles in discharge planning and care. Discharge program and intervention models, and ways to incorporate discharge interventions into advanced practice in acute care hospitals, are di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…[166][167][168][169][170] Clinical nurse specialists are also active in discharge planning, which prepares patients and families for the next phase of care and assists in making arrangements for that transition. 128,[171][172][173][174][175][176][177][178][179] Last, CNSs coordinate care by providing direct community follow-up by way of home visits or through telephone management. 172,[180][181][182][183][184][185] This latter aspect of CNS practice emerged in the literature over the past 2 decades, with the trend in healthcare of early discharge from acute care settings.…”
Section: First Substantive Area: Manage the Care Of Complex And/or Vumentioning
confidence: 99%
“…[166][167][168][169][170] Clinical nurse specialists are also active in discharge planning, which prepares patients and families for the next phase of care and assists in making arrangements for that transition. 128,[171][172][173][174][175][176][177][178][179] Last, CNSs coordinate care by providing direct community follow-up by way of home visits or through telephone management. 172,[180][181][182][183][184][185] This latter aspect of CNS practice emerged in the literature over the past 2 decades, with the trend in healthcare of early discharge from acute care settings.…”
Section: First Substantive Area: Manage the Care Of Complex And/or Vumentioning
confidence: 99%
“…To prevent early and unplanned readmission, health care providers should provide discharge planning. Depending on the hospital administration, discharge planning is done by primary care nurses, the health care team, nurses who function as discharge planners or social workers 16 …”
Section: Review Of Literaturementioning
confidence: 99%
“…By understanding factors associated with readmissions following cardiac surgery, clinicians can identify patients at the greatest risk for rehospitalization, implement effective interventions, and develop models to promote the quality of life and functional abilities of their patients as well as reduce rates of unplanned readmissions. Specific nursing strategies have been suggested to help prevent unplanned readmissions and include implementing a critical pathway, effective discharge planning, use of home health care, and follow‐up telephone calls 4–6,8,10,15,22 …”
Section: Nursing Strategies To Prevent Unplanned Readmissionsmentioning
confidence: 99%
“…There has been considerable controversy regarding length of stay (LOS) as a risk factor following cardiac surgery. Although some authors consider early discharge a risk factor for readmission, 10,12 four studies indicated that LOS was not a significant predictor for readmission 7,12,16,17 . In fact, Cowper et al 7 (n=83,347) found that death or cardiovascular readmission rates were less for those patients discharged early as compared with those with longer hospital stays.…”
mentioning
confidence: 99%